3D hollow Co–Fe–P nanoframes immobilized on N, P-doped CNT as an efficient electrocatalyst for overall water splitting. Issue 36 (10th September 2019) - Li, Wenxin; Chen, Yuanfu; Yu, Bo; Hu, Yang; Wang, Xinqiang; Yang, Dongxu
Abstract : The outstanding electrocatalytic performance of CoFeP NFs/NPCNT is attributed to its unique 3D hollow nanoarchitecture. Abstract : The rational design of nonprecious and high-efficiency bifunctional electrocatalysts with advanced structural and compositional preponderance for water electrolysis is of paramount importance for the generation of sustainable and clean energy. Herein, for the first time, a novel three-dimensional (3D) hollow hybrid electrocatalyst, Co–Fe–P nanoframe immobilized on N, P-doped carbon nanotubes (CoFeP NFs/NPCNT), was synthesized by selectively etching a CNT-composited Co, Fe-based Prussian blue analogue and subsequent phosphorization. Benefiting from its unique 3D hollow nanoarchitecture, which offers rich porosity and abundant catalytically active sites and guarantees excellent conductivity and structural stability, the hollow CoFeP NFs/NPCNT hybrid delivered pronounced catalytic activity for oxygen evolution (or hydrogen evolution) in alkaline electrolyte, with a low overpotential of 278 (or 132) mV at 10 mA cm −2, small Tafel slope of 39.5 (or 62.9) mV dec −1 and prominent long-term stability. Therefore, when CoFeP NFs/NPCNT was employed as the cathode and anode toward overall water-splitting, it required a quite small cell voltage of only 1.56 V to afford a current density of 10 mA cm −2, and displayed outstanding electrocatalytic stability over 60 h, greatly approaching the performance of the commercial Pt/C(−)//RuO2 (+) electrolyzer and outperforming most other non-noble-based electrolyzers.